AppSimV: A Cyber–Physical Simulation and Verification Platform for Software Applications of Intelligent Buildings - Haining Jia; Qiliang Yang; Ziyan Jiang; Wenjie Chen; Qizhen Zhou (Buildings, 2023)
Testing and verifying applications (Apps) are essential for a software-driven intelligent building system. Traditional methods connect App programs to hardware devices for debugging and testing on the engineering site. However, App bugs can hardly be found out before they are being deployed and thus always require an extended debugging cycle. To address this issue, we propose a cyber–physical simulation and verification platform named AppSimV, which enables the testing and verification of Apps in a mimic real scene. Taking swarm intelligence building as an example, this paper focuses on the cyber–physical architecture of AppSimV and its implementation mechanisms, including the standardized encapsulation of software components for the building physics model, a multitask scheduling simulation engine, a cyber–physical interaction interface, and the visual monitoring of the simulation process. The implementation mechanisms not only accurately simulate actual engineering scenarios but also facilitate the early detection and correction of issues that may arise during the App’s runtime, thus reducing the debugging time required for the App. With 1200 intelligent physical nodes connected in a swarm hardware system, AppSimV was validated by conducting the strict testing and verification of a set of Apps for an intelligent building. The results show that AppSimV is sound and reliable.